TRAIL mediated signaling in different cancers: cancer in the "Crosshairs" - Farooqi, Ammad Ahmad; Naureen, Humaira; Yilmaz, Seher; Sabitaliyevich, Uteuliyev Yerzhan; Zhailganov, Azamat; Rabandiyarov, Marat; Ucak, Ilknur; Karasholakova, Lazzat; Attar, Rukset (Cellular and Molecular Biology, 2020)
Cancer is a therapeutically challenging disease because of its heterogeneous and multifaceted nature. Decades of research have sequentially and systematically enabled us to develop a sharper and better understanding of the heterogeneous nature of cancer. Genetic, genomic and proteomic studies have unraveled wide-ranging signaling cascades which play cornerstone role in disease onset and progression. More importantly, activation of pro-survival signaling and loss of apoptosis also play critical role in cancer progression. TRAIL-mediated signaling pathway has emerged as one of the most comprehensively analyzed cascade because of its exceptional ability to target cancer cells while leaving normal cells intact. TRAIL discovery and landmark achievements related to TRAIL/TRAIL-receptor signaling pathway attracted the attention of researchers. Therefore, scientists started to add missing pieces to an incomplete jig-saw puzzle and allowed contemporary researchers to conceptualize a better molecular snapshot of TRAIL-induced signaling in various cancers. Circumstantial evidence illuminated a functionally unique "push and pull" between anti-apoptotic and pro-apoptotic proteins in different cancers. Overexpression of anti-apoptotic proteins and inactivation of pro-apoptotic proteins shifted the balance towards loss of apoptosis. There has been a breakneck increase in the number of clinical trials related to TRAIL-based therapeutics which validate the true pharmacological potential of TRAIL-based therapeutics as effective anticancer agents. However, apart from advancements in our clinical understanding about the efficacy of TRAIL-based therapeutics, researchers have also faced setbacks in the field of translational medicine. Therefore, in this review, we have attempted to set spotlight on the most recent and landmark discoveries which have leveraged our understanding related to TRAIL-mediated signaling altogether to a new level.